2020
DOI: 10.3390/v12070736
|View full text |Cite
|
Sign up to set email alerts
|

Whole Genomic Analysis and Comparison of Two Canine Papillomavirus Type 9 Strains in Malignant and Benign Skin Lesions

Abstract: Papillomaviruses (PVs) usually cause benign proliferative lesions in the stratified epithelium of various animal species. However, some high-risk types of PVs have been proven to lead to malignant transformations. In dogs, several canine papillomaviruses (CPVs) have been identified in malignant lesions and are suggested as one of the risk factors for the development of squamous cell carcinomas (SCCs). In the present study, the full genomes of two CPV9 strains from recurrent SCCs of Dog 1 and skin viral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…Results of the histopathological differential diagnosis examination, characteristic superficial vacuolated (koilocytic) keratinocytes specific to the pathogenesis of CPV infection were observed as a typical finding in productive papillomavirus infections. Histopathological examination revealed hyperpigmentation and proliferation in the ephitelia, eosinophilic intra-nuclear inclusion bodies in the stratum granulosum, invasion in stroma, keratinization and polymorphism in the nucleus, as described previously by others (Nicholis et al, 1999;Martins et al, 2008;Platter and Holstetter, 2009;Tekelioglu et al,2017;Chang et al, 2020).In contrast with the findings of Bianchi et al (2012), intranuclear inclusion bodies were observed in all cases.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Results of the histopathological differential diagnosis examination, characteristic superficial vacuolated (koilocytic) keratinocytes specific to the pathogenesis of CPV infection were observed as a typical finding in productive papillomavirus infections. Histopathological examination revealed hyperpigmentation and proliferation in the ephitelia, eosinophilic intra-nuclear inclusion bodies in the stratum granulosum, invasion in stroma, keratinization and polymorphism in the nucleus, as described previously by others (Nicholis et al, 1999;Martins et al, 2008;Platter and Holstetter, 2009;Tekelioglu et al,2017;Chang et al, 2020).In contrast with the findings of Bianchi et al (2012), intranuclear inclusion bodies were observed in all cases.…”
Section: Discussionsupporting
confidence: 78%
“…In this study, it was observed that an aggressive nonregressive pathogenesis occurred in the tissues examined and the basement membrane was also affected by the infection. It has been stated that similar aggressive pathogenesis may occur in infections caused by HPV 11, 16 and 18 subtypes, which are associated with airway malignancies, especially in humans (Martins et al, 2008;Chang et al, 2021).Particular types of papillomaviruses are associated with squamous cell carcinomas in dogs and cancer of cervix, anus and pharynx in humans (Muphy et al, 1999;Martins et al, 2008;Wang et al, 2010;Chang et al, 2020;Gürgen et al, 2021).The relationship of canine papillomaviruses with squamous cell carcinoma and other malignancies in the field of veterinary medicine is still not fully elucidated and studies are ongoing.…”
Section: Discussionmentioning
confidence: 98%
“…Although all CPV types have the E6 and E7 oncoproteins, more studies should be done to elucidate the role of each CPV type in respect of cancer development risk, and the role of these oncoproteins in the progression of pre-neoplastic lesions to a malignant neoplasia. In this context, to the best of our knowledge, only CPV1, CPV2, CPV3, CPV7, CPV9, CPV12, CPV15, CPV16, and CPV17 have been isolated in cases of cancer ( Lange et al, 2016 ; Thaiwong et al, 2018 ; Chang et al, 2020b ).…”
Section: Genome and Infection Cyclementioning
confidence: 99%
“…Analysis of CPV9 genomes isolated from benign and malignant SCC lesions showed that the nucleotide sequence of the virus from the malignant lesion presents a 328 bp deletion at the 3’end in the gene E2. In cases of cancer due to HPV, E2 deletion results in an increase in E6 and E7 protein expression; however, in a case of SCC due to CPV9 no change in the mRNA expression of E6 and E7 was found, indicating that other mechanisms were responsible, for example, differences in protein translation or stability ( Chang et al, 2020 b).…”
Section: Genome and Infection Cyclementioning
confidence: 99%
“…CPV is a virus that belongs to the family of papillomaviruses with the ability to generate squamous cell carcinomas (SCCs) in dogs. The whole genomes of two CPV type 9 (CPV9) strains from recurrent SCCs isolated from benign or malignant skin lesions of two dogs were successfully analyzed by Chang et al [7]. The obtained findings suggest that E2 protein and chimeric protein E8ˆE2 deleted CPV9 have a potential role in the oncogenesis of benign and malignant lesions; however, this role should be comprehensively explored in further experiments.…”
mentioning
confidence: 99%